A comparison of three statistical methods applied in the identification of eating patterns Comparação de três métodos estatísticos aplicados na identificação de padrões alimentares - Diana Barbosa Cunha; Renan Moritz Varnier Rodrigues de Almeida; Rosângela Alves Pereira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
This work aimed to compare the results of three statistical methods applied in the identification of dietary patterns. Data from 1,009 adults between the ages of 20 and 65 (339 males and 670 females) were collected in a population-based cross-sectional survey in the Metropolitan Region of Rio de Janeiro, Brazil. Information on food consumption was obtained using a semi-quantitative food frequency questionnaire. A factor analysis, cluster analysis, and reduced rank regression (RRR) analysis were applied to identify dietary patterns. The patterns identified by the three methods were similar. The factor analysis identified "mixed", "Western", and "traditional" eating patterns and explained 35% of the data variance. The cluster analysis identified "mixed" and "traditional" patterns. In the RRR, the consumption of carbohydrates and lipids were included as response variables and again "mixed" and "traditional" patterns were identified. Studies comparing these methods can help to inform decisions as to which procedures best suit a specific research scenario. O objetivo deste estudo foi comparar três métodos estatísticos empregados na identificação de padrões alimentares. Foram utilizados dados de 1.009 adultos de 20 a 65 anos de idade (339 homens e 670 mulheres) coletados em estudo transversal de base populacional desenvolvido na Região Metropolitana do Rio de Janeiro, Brasil. Para a identificação de padrões alimentares foram aplicadas a análise fatorial, análise de cluster e a reduced rank regression analysis (RRR). Os três métodos identificaram padrões alimentares similares. A análise fatorial identificou os padrões "misto", "ocidental" e "tradicional", que explicaram 35% da variância total. Pela análise de cluster, foram identificados dois padrões "misto" e "tradicional". Para a RRR, os consumos de carboidratos e de lipídeos foram incluídos como variáveis respostas e também foram identificados os padrões "misto" e "tradicional". A comparação desses métodos auxilia na definição do procedimento mais adequado para um cenário de pesquisa específico.